Clinical course, complications, immunization status and outcome of mumps in children - Mir, Naseer Yousuf; Wani, Jawad Nazir; Farooq, Wamiq; Zaman, Bashir U. (International Journal Of Community Medicine And Public Health, 2023)
Background: Mumps is a self-limiting viral disease in children which usually resolve within 10 days. It is characterized by fever, constitutional symptoms and swelling of the parotid gland(s) and may lead to serious complications. The most common complication is orchitis, followed by meningitis. Less common complications include pancreatitis, encephalitis, deafness, mastitis, oophoritis, and facial Bell palsy. Methods: This is a hospital-based Prospective observational study where children age ≤18 years who presented with mumps were studied for immunization status, clinical course, complications and outcome. Results: Fever was the most common presentation followed by parotid involvement. The mean duration of illness was 9±2 days. Constitutional symptoms like headache, myalgia or fatigue were seen in 90 patients (60%). The most common complication seen was orchitis and tonsilitis, 4 cases (2.7%) each followed by pancreatitis (2%), febrile seizures (2%) and meningitis (2%). The least common was myocarditis (0.7%). Only 10 (6.7%) of the patients were hospitalized and none died. All the patients were cured within 2 weeks and without any sequels. The average loss of school days (school absentee) were 8 days. These complications were seen only in non- immunized patients. Conclusions: The benefits of vaccination against mumps in addition to rubella and measles would be a logical public health intervention that would have a significant clinical and economic benefits and to prevent complications of mumps.